Theoretical Model of Coronary Blood Flow Regulation: Role of Myocardium Compressive Forces. (November 2015) - Xie, Xinzhou; Wang, Yuanyuan
Abstract: Objective: Auto‐regulatory reserve of coronary blood flow is nonuniformly distributed across the ventricular wall. MCF are thought to play an important role in determining the transmural distribution of myocardium blood flow. Here, impacts of MCF on coronary flow regulation are analyzed using a theoretical model. Methods: Coronary microvessels at various depths in the ventricular wall are represented by parallel segments. Nine vessel regions are connected in series to represent one parallel segment, which includes four vasoactive regions regulated by the wall tension, the shear stress and the metabolic demand. The nonuniform distribution of MCF is modeled and its effects on coronary flow regulation are taken into consideration by using a modified tension model and a vessel collapse model. Flow regulation behaviors in both normal and obstructed coronary circulation are simulated. Results: Model‐predicted auto‐regulatory curve is shifted to the high pressure region by including the effect of MCF. Model‐predicted flow distributions in obstructed coronary circulation show that severe stenosis in coronary artery would first impede myocardial blood flow in subendocardial layer. Conclusions: The model results indicate that MCF plays an important role in coronary flow regulation and also in determining the transmural distribution of myocardium blood flow.